Aspiration pneumonia in children: an iconographic essay - Oliveira,Gabriel Antonio de (2015)
Abstract In most cases of aspiration pneumonia in children, the disease is specific to this age group. Clinical and radiological correlation is essential for the diagnosis. The present pictorial essay is aimed at showing typical images of the most common etiologies.